Preparation of Single Chain Nanoparticles via Photoinduced Double Collapse Process - Dashan, Irem; Balta, Demet Karaca; Temel, Binnur Aydogan; Temel, Gokhan (WILEY-V C H VERLAG GMBH, 2019)
A straightforward method is described to achieve polymeric nanoparticles by double folding of single linear chains. The side chain functional polystyrene with controlled molecular weight is converted to pendant azide and benzophenone motifs via postmodification reactions. Resulting functionalized chains undergo intramolecular crosslinking upon ultraviolet (UV) illumination using simultaneous and subsequent pathways at a dilute concentration. Particle size of nanoparticles can be tuned by changing the degree of crosslinking using a second folding process. Obtained single and double collapsed chains indicate higher glass transition temperatures and lower hydrodynamic radii compared to their intermediates. To our knowledge, the combination of photoinduced azide crosslinking and radical coupling processes is the first attempt to prepare double folding single polymer chains.
Keywords: controlled radical polymerization; double collapse; photoinduced crosslinking; polymeric nanoparticles; single-chain nanoparticles; INTRAMOLECULAR CROSS-LINKING; COVALENT; STRATEGY; COMPLEX; ROUTE; Polymer Science